MARKERS OF INFLAMMATION AND ANTIOXIDANT PROTECTION IN THE ORAL FLUID OF CHILDREN WITH DIFFERENT BODY MASS INDEX BEFORE AND AFTER THE USE OF THE THERAPEUTIC AND PROPHYLACTIC COMPLEX - Reyzvikh, O.E.; Sukhomeylo, D.O.; Shnaider, S.A.; Klenovskaya, S.V.; Romanova, Y.H. (World of Medicine and Biology, 2021)
It is known that the inflammatory reaction performs a protective function in the body. Applications of a mucosoadhesive gel containing lipopolysaccharide are proposed in order to enhance the inflammatory response and activate leukocytes migrated into the parodontium. Thus, the inflammatory process does not have the ability to become chronic. A method for the treatment of inflammatory parodontal diseases in children of 12 years old has been developed, substantiated and tested, which provides for the use of a complex of anti-inflammatory adaptogens, the effectiveness of which is confirmed by the normalization of the oral microbiocenosis (a decrease in the degree of dysbiosis by 2.1–4.2 times to normal values), a decrease in the activity of inflammatory processes (elastase by 2 times, malondialdehyde by 1.7 times), restoration of antimicrobial protection (decrease in urease activity by 1.4–2 times; increase in lysozyme levels by 1.6–1.7 times) in the oral cavity of children as with hypo- and with hypertrophy. The obtained results indicate the absence of inflammatory processes and demonstrate the high therapeutic and prophylactic efficacy of the proposed complex.
Keywords: children; inflammation; body mass index; oral fluid; treatment-and-prophylactic complex; dental diseases